2014
DOI: 10.1242/jeb.106666
|View full text |Cite
|
Sign up to set email alerts
|

Female gray treefrogs, Hyla versicolor, are responsive to visual stimuli but unselective of stimulus characteristics

Abstract: The visual ecology of nocturnal anurans is poorly understood, but there is growing evidence that vision plays a role in important behaviors such as mate choice. While several recent studies have demonstrated that females are responsive to visual cues when selecting mates, the forces responsible for these preferences are unknown. We investigated the responsiveness of female gray treefrogs, Hyla versicolor, to video playbacks of calling conspecific males in which we varied attributes of the vocal sac, a conspicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…This suggests that mate choice, at least in the Gray Treefrogs tested here, is mediated predominantly by acoustic cues. This is in line with previous studies on multimodal communication in this species, that showed that although females are not indifferent to visual cues colocalized with an acoustic signal (Reichert & Höbel, 2015), there is no evidence for visual mate choice (Reichert et al, 2014).…”
Section: Experiments 2: Dynamic Light Pollutionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that mate choice, at least in the Gray Treefrogs tested here, is mediated predominantly by acoustic cues. This is in line with previous studies on multimodal communication in this species, that showed that although females are not indifferent to visual cues colocalized with an acoustic signal (Reichert & Höbel, 2015), there is no evidence for visual mate choice (Reichert et al, 2014).…”
Section: Experiments 2: Dynamic Light Pollutionsupporting
confidence: 92%
“…However, there is substantial between‐species variation in the use of visual cues, as well as the relative reliance on visual versus acoustic signal components. In H. versicolor , visual mate choice is weak (Reichert, Galante, & Höbel, ; Reichert & Höbel, ), and we therefore expect that females would not attend more to visual cues under increased light levels. Nevertheless, there are species that do attend to visual cues (Gomez et al., ; Taylor et al., ), and for them increased nocturnal light should facilitate the use of inter‐ or intrasexual displays.…”
Section: Discussionmentioning
confidence: 99%
“…Details of video stimulus preparation can be found in Reichert et al. (). Briefly, the animated frog stimuli consisted of a still image of a male H. versicolor with an appended image of a vocal sac that was animated to mimic the inflation and deflation that takes place during the production of a natural advertisement call (see Supporting Information Movie S1 in Reichert et al.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in a video playback experiment, females showed phototaxis to a variety of visual stimuli presented on a computer monitor (Reichert et al. ).…”
mentioning
confidence: 99%
“…All experiments were performed in a darkened semi-anechoic chamber (for further details of the testing arena, see Reichert et al, 2014). Females were placed in an acoustically transparent release cage in a circular arena 1 m from each of the playback speakers.…”
Section: Test Proceduresmentioning
confidence: 99%